Temporalités des performances aux tests de raisonnement inductif chez des élèves ivoiriens selon leurs caractéristiques individuelles - Gustave, KOFFI Franck (International Journal of Social Sciences, Language and Linguistics, 2025)
The aim of the study is to examine the influence of time on inductive reasoning in students of different genders, ages and chronotypes. 240 students were given a session of inductive reasoning tests (MGM : Playing Card Test and the B53 : Logical Sequence Test) as well as the Caci et al. (2005) Maturity/Vesperity Scale at four times of the day (DM : early morning, FM ; late morning, DAM : early afternoon, FAM : late afternoon). The results, obtained using SPSS.20, indicate that while the inductive reasoning test performance of Ivorian pupils shows similar daily variations over the course of the day (two peaks and two troughs), it increases with the age and gender of the pupils, regardless of the time of day. In view of these results, this study could draw the attention of deputy heads of secondary schools to the importance of the temporalities of inductive reasoning in course scheduling, if they hope to get the best out of the students in their schools.